Feistel ciphers in East Germany in the communist era. Issue 5 (3rd September 2018) - Courtois, Nicolas; Drobick, Jörg; Schmeh, Klaus
ABSTRACT: Feistel ciphers (balanced and unbalanced) represent the most popular symmetric cipher type in modern cryptography. The invention of Feistel ciphers is usually credited to IBM's Horst Feistel, who co-created the first publicly known encryption algorithm of this type, Lucifer, in the early 1970s. In this publication, the authors will show that Feistel ciphers (or at least a very similar concept) played a surprisingly important role in East Germany in the last two decades of the communism era (i.e., between 1970 and 1990). They will introduce four Feistel ciphers developed by East German cryptologists during these two decades. This includes an unbalanced Feistel cipher that predated RC2, the oldest unbalanced Feistel cipher known in the crypto community (by over a decade), as well as an East German DES variant.